Preserving Local Wisdom Through Extensive Reading Book “Traditional Games Of Indigenous People In West Kalimantan” - Ana Fergiana; Melti Oktavianda (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aims to develop Extensive Reading books as learning materials for undergraduate students and to preserve the culture of traditional games that for decades have been performed by indigenous people in West Kalimantan yet are now being overlooked. The researchers believe that by developing a book based on local wisdom, students will be motivated to read the book because it is in accordance with their cultural identity. The researchers focused on the first three steps of the ADDIE model proposed by Branch (2009), namely Analyse, Design, and Develop. In the Analyse section, 50 students were invited to participate in need analysis in which they were asked several questions in the form of interviews and questionnaires. The results of need analysis were particularly accommodating to ascertain the level of difficulty of the text, student expectations, writing format and book content in the Design step. In the Develop step, the researchers produced an Extensive Reading book entitled